The Mixpoem Program. - Laughlin, James; Kenner, Hugh (Paris Review)
This article discusses the Mixpoem Program. The mixpoem started with James Laughlin's curiosity about every possible arrangement of the words in Ezra Pounds "In a station of the Metro." A computer program was created to help with this process. The computer program used was called BASIC. Then updated once a colleague advised a better program called Trotter Algorithm.